Pola Penggunaan Obat Mood Stabilizer Pada Pasien Bipolar di Rumah Sakit Jiwa Daerah Atma Husada Mahakam - Annida Rifaya; Risna Agustina; Rolan Rusli (Proceeding of Mulawarman Pharmaceuticals Conferences, 2019)
Bipolar disorder is a chronic mood disorder characterized by episodes of mania or hypomania that occur alternately or mixed with depressive episodes. This study aims to determine the characteristics of bipolar patients and patterns of drug use inpatient and outpatient bipolar patients at Atma Husada Mahakam Hospital. The type of this research is non experimental (descriptive) and done retrospectively. Data are collected from medical record. Research subjects were 84 inpatients and 137 outpatients with bipolar disorder diagnosis. Data are analyzed by describing research's objects. The results were obtained from inpatient and outpatient data showing 63% and 60% female sex, showing 26-35 years (early adulthood), not working, not married, and high school level education. The most usage pattern of drugs is a combination of 2 and 3 drugs, namely 74.99% for inpatient care and 73.71% for outpatient treatment. The drugs most commonly used are mood stabilizers (valproate acid) and atypical antipsychotics (risperidone).